It`s never simple! People, power and relationships in the United Kingdom Olympic sport policy system. A commentary - Moore, L.; Oakley, B.; Twitchen, A. (Journal of Sports Sciences, 2025)
Drawing on insights from the United Kingdom [UK], this commentary highlights the complexity of the Olympic sport policy process and proposes a novel conceptual approach that situates people at the forefront of the analysis. Informed by process sociology, the approach demonstrates the importance of understanding complexity as the consequence of interdependent relationships that bind people together. Extracts from interviews undertaken with nine senior National Governing Body employees, who are responsible for implementing Olympic sport policy, are drawn on to inform and illuminate the proposed approach. Their extracts showcase that conversations and dialogue, often undertaken in the context of meetings, are central to the policy process. Managing emotions, navigating opacity, deep personal involvement and associated personal wellbeing impacts are all features of the Olympic sport policy process not readily accounted for in the extant literature or practice. The process, increasingly games like, never wholly represents the actions of any one group or individual as they navigate choices constrained by the interlacing of many relationships over time. We therefore conclude that it may be conceptually better to now describe the organisation of Olympic sport in the UK as a figuration of people rather than as a "system".